2019
DOI: 10.1161/jaha.119.012341
|View full text |Cite
|
Sign up to set email alerts
|

ATRQβ‐001 Vaccine Prevents Experimental Abdominal Aortic Aneurysms

Abstract: BackgroundWe have developed a peptide vaccine named ATRQβ‐001, which was proved to retard signal transduction initiated by angiotensin II (Ang II). Ang II was implicated in abdominal aortic aneurysm (AAA) progression, but whether the ATRQβ‐001 vaccine would prevent AAA is unknown.Methods and ResultsAng II‐infused ApoE−/− mice and calcium phosphate‐induced AAA in C57BL/6 mice were used to verify the efficiency of ATRQβ‐001 vaccine in AAA. Results demonstrated that the vaccine effectively restrained the aneurysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…In Liao's et al studies, the ATRQβ-001 vaccine could effectively decrease the blood pressure in the AngII induced hypertension mice and spontaneous hypertensive rats (SHRs) (Chen et al, 2013). The team also used ATRQβ-001 to treat AngII or calcium phosphateinduced abdominal aortic aneurysm (Zhang et al, 2019). The results showed that ATRQβ-001 could reduce blood pressure and inhibit the expansion of aneurysm and the destruction of the aortic wall in both models.…”
Section: Peptidesmentioning
confidence: 99%
“…In Liao's et al studies, the ATRQβ-001 vaccine could effectively decrease the blood pressure in the AngII induced hypertension mice and spontaneous hypertensive rats (SHRs) (Chen et al, 2013). The team also used ATRQβ-001 to treat AngII or calcium phosphateinduced abdominal aortic aneurysm (Zhang et al, 2019). The results showed that ATRQβ-001 could reduce blood pressure and inhibit the expansion of aneurysm and the destruction of the aortic wall in both models.…”
Section: Peptidesmentioning
confidence: 99%
“…ATRQβ-001 vaccine and McAb-ATR were prepared as previously described. 21,22 Briefly, ATR-001 peptide (C-A-F-H-Y-E-S-Q) with a purity above 98% was synthesized and validated by GL Biochem Ltd (Shanghai, China). Qβ viruslike particle (VLP) was expressed and purified, then identified using SDS-PAGE and transmission electron microscopy.…”
Section: Vaccine Preparation and Antibody Productionmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis, quantitative real-time PCR (qRT-PCR), protein extraction, and western blotting were performed as previously described. 22 The primer sequences are listed in the Table S1. Cycle quantification (Cq) values of qRT-PCR were normalized by 18srRNA, calculated using the 2 −ΔΔCq method, and compared as arbitrary units.…”
Section: Mrna and Protein Analysismentioning
confidence: 99%
See 2 more Smart Citations